Case Report: Healing a Traumatic Birth - Klaus, Phyllis (Frontiers in Psychology, 2020)
One needs to recognize that the perinatal period is a vulnerable time where negative attitudes, words and actions can have an emotionally damaging effect on birthing women, who are especially sensitive to how they are treated, because of their high oxytocin levels. This case report depicts a traumatic birth in which the mother was needlessly separated from her baby and also harshly treated by the personnel, which had an emotionally devastating impact on the mother/baby relationship. This case report will demonstrate how psychotherapy was used to heal this distress.